MY KID SPENDS MUCH TIME ON TIKTOK: EFEKTIVITAS MODIFIKASI PERILAKU DENGAN TOKEN EKONOMI DALAM KONTROL DURASI PENGGUNAAN TIKTOK - Musalmah, Indria; Pabela, Tiara; Kurniawan, Aldo; Elvika, Rahmah R.; Taslim, Fauziah (Universitas Gunadarma, 2024)
TikTok social media addiction is one of the phenomena that is increasing today and has a major impact on daily life. To reduce this addiction, this study uses a behavior modification technique, namely token economy. The token economy is a behavior modification system that utilizes the principle of reinforcement in the form of tokens to increase the desired behavior. The economic tokens used are star stickers that will be given during the intervention phase. The research method used is a single case experiment with an A-B research design which is divided into 2 phases, namely the baseline phase (A) and the Intervention phase (B). The subject is a 14-year-old teenager who uses TikTok social media a lot. The results showed that the application of the token economy succeeded in reducing the duration of playing TikTok social media from an average of 6 hours a day to 2 hours a day